Ellul on New Urbanism - Wang, David (Christian scholar's review, 2009)
In this paper, Jacques Ellul’s theory of “technique” and his theology of the city are framed into a critique of New Urbanism. Against Modernism’s view of the city as a “machine for living in,” New Urbanism harks back to the ambiance of old New England towns. But far from assuring the sense of community it promotes, Ellul’s thought reveals this new paradigm to be as mechanistic as the one it replaces. The paper concludes by highlighting three Ellulian suggestions towards more authentic expressions of sense of community. Dr. David Wang is professor of architecture at Washington State University Spokane.